AKUNTABILITAS KEPALA MADRASAH DALAM MENINGKATKAN PROFESIONAL GURU DI MADRASAH ALIYAH NEGERI 2 TANJUNG JABUNG TIMUR - Aziz; Maisah; M. Syahran Jailani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the accountability of the madrasa principal in improving teacher professionalism at MAN 2 Tanjung Jabung Timur. The study is based on the identification of several issues, including inconsistent supervision, incomplete performance documentation, limited evaluation of professional development programs, and uneven improvement in teachers’ pedagogical and technological competencies. This study employs a qualitative approach using observation, interviews, and documentation as data collection techniques. The findings indicate that the principal’s accountability is reflected through program planning, academic supervision, performance monitoring, and transparent policy implementation. The inhibiting factors include inconsistency in supervision, limited use of learning technology by some teachers, insufficient teacher involvement in program planning, and weak continuous evaluation. The efforts undertaken by the principal include strengthening supervision, conducting intensive teacher training, optimizing MGMP activities, improving transparent performance documentation, and building a collaborative work culture. The study concludes that the accountability of the madrasa principal plays a strategic role in enhancing teacher professionalism, although further reinforcement is required in aspects of evaluation, transparency, and teacher participation in professional development programs.